PENERAPAN ARSITEKTUR METAFORA DALAM REDESAIN PASAR WISATA PLAOSAN KABUPATEN MAGETAN - Annisa' Qurrotu'aini; Sumaryoto Sumaryoto; Ofita Purwani (ARSITEKTURA, 2017)
Plaosan Tourism Market is the only tourism market at Magetan. This market has a potential to be a tourism destination at Magetan because it is located on the tourist route that head towards the popular attractions in Magetan. However this market is not a real tourism market as it does not meet the requirements for tourist destination which include attractions and facilities. This market does not use the potential of the area provided as attractions, even though Magetan is famous for farming and home industries. The market does not have primary and ancillary facilities to fulfill the tourism aspect. Besides the lack of attractions and facilities, the architecture of the market needs something unique on its design to attract the tourists. The design method used to redesign Plaosan Tourism Market is metaphoric architecture, because it can representate and show unique image, so it can attract tourists. The main problems in planning and designing Plaosan Tourism Market with metaphoric architecture approach ie what kind of attractions are needed in Plaosan Tourism Market, how the concept of facilities that requires tourism aspect, what form it will be used as basis of analogy that represents tourist destinations in Magetan, how to transform the base concept to be a tourism market design with metaphoric architecture. The planning and designing of Plaosan Tourism Market with metaphoric architecture approach use creative thinking method which consists of synthesising, elaborating, and imagining. Based on questionnaries, preferred objects to represent Magetan are Sarangan lake, leather handicrafts, Lawu mountain, and Batik Pringsedaphur, all of which will be to the main idea for the design by turning them into metaphor in designing this tourism market.